A proposed framework for the interpretation of biomonitoring data - Boogaard Peter; Money Chris (BMC, 2008)
Abstract Biomonitoring, the determination of chemical substances in human body fluids or tissues, is more and more frequently applied. At the same time detection limits are decreasing steadily. As a consequence, many data with potential relevance for public health are generated although they need not necessarily allow interpretation in term of health relevance. The European Centre of Ecotoxicology and Toxicology of Chemicals (ECETOC) formed a dedicated task force to build a framework for the interpretation of biomonitoring data. The framework that was developed evaluates biomonitoring data based on their analytical integrity, their ability to describe dose (toxicokinetics), their ability to relate to effects, and an overall evaluation and weight of evidence analysis. This framework was subsequently evaluated with a number of case studies and was shown to provide a rational basis to advance discussions on human biomonitoring allowing better use and application of this type of data in human health risk assessment.